DETERMINASI STRUKTUR MODAL PADA PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2016 - Hasbullah, Iman Indrafana Kusumo (TIN: Terapan Informatika Nusantara, 2020)
This study aims to determine the effect of asset structure, profitability, liquidity, sales growth, firm size and business risk to capital structure in property and real estate firms listed on the BEI. This study uses pecking order theory and trade-off theory. The research design used is the causality to examine the effect of variables. The sampling technique used purposive sampling and yielded 22 samples for 5 periods. This study uses secondary data and data collection techniques using documentation study. Analytical technique used multiple linear regression. The obtained results are the assets structure has a significant negative effect on capital structure and liquidity has a significant negative effect on capital structure. While profitability does not have significant effect to capital structure, growth of sales does not have significant effect to capital structure, firm size does not have significant effect to capital structure and business risk does not have significant effect to capital structure